The ethics and religious philosophy of Etty Hillesum : proceedings of the Etty Hillesum Conference at Ghent University, January 2014 - Smelik, K. A. D., 1950- (Supplements to The Journal of Jewish Thought and Philosophy, 2017)
The Ethics and Religious Philosophy of Etty Hillesum contains the proceedings of the second international Etty Hillesum Congress at Ghent University in January 2014 and is a joint effort by fifteen Hillesum experts to shed new light on the life, works and vision of the Dutch Jewish writer Etty Hillesum (1914-1943), one of the victims of the Nazi-regime. Hillesum's diaries and letters illustrate her heroic struggle to come to terms with her personal life in the context of the Holocaust. This volume revives Hillesum research with a comprehensive rereading of her texts. With the current rise of interest in peace studies, Judaism, the Holocaust, inter-religious dialogue, gender studies and mysticism, it is evident that this book will be invaluable to students and scholars in various disciplines.